The impact of medication adherence on health outcomes for patients with metabolic syndrome - Setiawan, Christianus Heru; Virginia, Dita Maria; Pinaryanto, Kartono; Sari, Lisa Kurnia; Hendra, Phebe (JURNAL ILMU KEFARMASIAN INDONESIA, 2024)
Cardiovascular disease is a non-communicable disease that is often associated with metabolic syndrome (MetS). MetS is a group of abnormal conditions that include hypertension, obesity, and diabetes. Patients with MetS often require multiple drugs to achieve therapeutic targets, but poor medication adherence can lead to complications. Poor medication adherence can worsen the disease and increase hospitalizations. The purpose of this study was to investigate whether medication adherence affects metabolic syndrome outcomes. This study was conducted using a cross-sectional design and purposive sampling. Our respondents were focused on patients with hypertension, diabetes mellitus, or dyslipidemia. Patients' adherence was measured using a self-made questionnaire. The study obtained data on the patient's lipid profile, HbA1c, and blood pressure (hypertension, diabetes, or dyslipidemia). The study used Spearman analysis to investigate adherence scores to lipid profile levels, HbA1c, and blood pressure. Therapeutic coverage was analyzed using a T-test. Confounding variables, such as age, HbA1c level, and blood pressure, were considered when analyzing the correlation between adherence scores and lipid profiles. The majority of patients were women or elderly, and more than 90% reported that their therapeutic needs were met. Total cholesterol and LDL-c significantly negatively correlated with adherence for patients' factor category, therapeutic regimen factor, and overall factor (p<.05). Triglyceride levels correlated significantly with adherence only to category interaction factors between patients and family/health workers. Regression analysis shows that all correlations are negative to total cholesterol, LDL, HDL, and triglyceride levels (p<.05).